Periodicity computation of generalized mathematical biology problems involving delay differential equations - Jasim Mohammed, M.; Ibrahim, R.W.; Ahmad, M.Z. (Elsevier, 2017)
In this paper, we consider a low initial population model. Our aim is to study the periodicity computation of this model by using neutral differential equations, which are recognized in various studies including biology. We generalize the neutral Rayleigh equation for the third-order by exploiting the model of fractional calculus, in particular the Riemann–Liouville differential operator. We establish the existence and uniqueness of a periodic computational outcome. The technique depends on the continuation theorem of the coincidence degree theory. Besides, an example is presented to demonstrate the finding.